Assessing the sustainability of the components emerging from the urban development strategy (CDS) from the perspective of residents (case example: Ardabil city) - mohammad hasan yazdani; samira saeidi zaranji; kamran dolatyariyan (تحقیقات کاربردی علوم جغرافیایی)
Urban development strategy represents a contemporary approach in urban planning and management, offering a framework for achieving sustainable urban development through poverty reduction, citizen participation, and increased investment. Like many cities in Iran, Ardabil faces numerous challenges, including inadequate governance, deteriorating infrastructure, substandard housing, weak public utilities, and insufficient social and health services. These issues underscore the necessity of strategic planning to address urban development effectively. This study aims to evaluate the indicators of urban development strategy in Ardabil. Employing a descriptive-analytical methodology, the research is grounded in field investigations. A sample size of 230 participants was determined using Sample Power software. Data analysis was conducted using one-sample T-tests and structural equation modeling (SEM) in AMOS Graphics software. The results of the one-sample T-test revealed that the status of urban development strategy indicators—livability, good governance, bankability, and competitiveness—in Ardabil is suboptimal, with mean scores of 2.21, 2.6, 2.62, and 2.15, respectively. Second-order factor analysis indicated that among the dimensions of urban development strategy, competitiveness, with a factor weight of 0.93, exerts the most significant influence, while bankability, with a factor weight of 0.62, has the least impact. Furthermore, the findings demonstrated that an improvement in the good urban governance index leads to a 0.55 increase in bankability, a 0.76 increase in livability, and a 0.86 increase in competitiveness. These results highlight the interconnectedness of governance quality with other dimensions of urban development, emphasizing the need for integrated strategies to enhance Ardabil's urban sustainability.